Israel : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1997)
Contents include: Budget deficit - concepts, measurements, and developments; definition, accounting basis, scope, and coverage. Structural reform issues: privatization; capital market reform; exchange and trade liberalization; other government intervention - investment subsidies and price controls; labor market reform; and land reform. Current account sustainability in Israel: overview of the Israeli economy and its transformation in the 1990s; a model of the current account applied to Israel; and sustainability indicators. Statistical tables.